Fast implementation for compressive recovery of highly accelerated cardiac cine MRI using the balanced sparse model. Issue 4 (5th April 2016) - Ting, Samuel T.; Ahmad, Rizwan; Jin, Ning; Craft, Jason; Serafim da Silveira, Juliana; Xue, Hui; Simonetti, Orlando P.
Abstract : Purpose: Sparsity‐promoting regularizers can enable stable recovery of highly undersampled magnetic resonance imaging (MRI), promising to improve the clinical utility of challenging applications. However, lengthy computation time limits the clinical use of these methods, especially for dynamic MRI with its large corpus of spatiotemporal data. Here, we present a holistic framework that utilizes the balanced sparse model for compressive sensing and parallel computing to reduce the computation time of cardiac MRI recovery methods. Theory and Methods: We propose a fast, iterative soft‐thresholding method to solve the resulting ℓ 1 ‐regularized least squares problem. In addition, our approach utilizes a parallel computing environment that is fully integrated with the MRI acquisition software. The methodology is applied to two formulations of the multichannel MRI problem: image‐based recovery and k‐space‐based recovery. Results: Using measured MRI data, we show that, for a 224 × 144 image series with 48 frames, the proposed k‐space‐based approach achieves a mean reconstruction time of 2.35 min, a 24‐fold improvement compared a reconstruction time of 55.5 min for the nonlinear conjugate gradient method, and the proposed image‐based approach achieves a mean reconstruction time of 13.8 s. Conclusion: Our approach can be utilized to achieve fast reconstruction of large MRI datasets, thereby increasing the clinical utility of reconstruction techniques based on compressed sensing. Magn Reson Med 77:1505–1515, 2017. © 2016 International Society for Magnetic Resonance in Medicine